PERLINDUNGAN HAK ANAK DALAM KONFLIK BERSENJATA DI KONGO BERDASARKAN CONVENTION ON THE RIGHTS OF THE CHILD 1989: Protection Of Children's Rights In Congo’s Armed Conflict Based On Convention On The Rights Of The Child 1989 - Juwita Leovani; Andrey Sujatmoko (Reformasi Hukum Trisakti, 2024)
The armed conflict, particularly in the Eastern Congo regions of North Kivu, South Kivu and Ituri, has led to many violations of children's rights. 14.9 million children have been most severely affected by this conflict. There are violations in terms of recruitment, use, detention, abduction, physical and sexual violence, attacks on schools and health facilities. The formulation of the problem of this article is what forms of violations of children's rights in the armed conflict that occurred in Congo based on the UNCRC 1989 and how efforts should be made by Congo in protecting children's rights based on the UNCRC 1989. This article uses normative research methods, descriptive-analytical in nature, drawing conclusions with deductive methods. The results of the research are the form of violations of children's rights committed by Congo, namely the right to survival, the right to protection, the right to growth and development and violating the principle of non-discrimination, the principle of state responsibility, the principle of the right to life and development to the fullest. The conclusion is that Congo should take the best measures to protect children's rights, especially in armed conflict, such as legislative, administrative, social and educational efforts to protect children's rights